2011
DOI: 10.1089/dna.2010.1046
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes on 9p21 Modify the Risk for Coronary Artery Disease Among Indians

Abstract: The chromosomal region 9p21 has been reported to be associated with myocardial infarction, coronary artery disease (CAD), diabetes, and many other related multifactorial diseases in humans. Although the genome-wide association studies have identified a limited number of single-nucleotide polymorphisms (SNPs) at 9p21 for CAD risk, the role of flanking SNPs has not been studied so far. Therefore, in the present work, we studied the role of flanking SNPs with respect to that of the previously identified SNPs rs10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The rs1333049 was identified in WTCCC GWA study as the strongest SNP associated with CAD risk (WTCCC, 2007). Although other variants at the 9p21 locus have been studied in Indians (Kumar et al, 2010;AshokKumar et al, 2011;Bhanushali et al, 2011;Maitra et al, 2009), no information is available to date on this variant. The results of our study determine for the first time the frequency of this SNP in the select population from Western India as well as confirm the association with CAD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs1333049 was identified in WTCCC GWA study as the strongest SNP associated with CAD risk (WTCCC, 2007). Although other variants at the 9p21 locus have been studied in Indians (Kumar et al, 2010;AshokKumar et al, 2011;Bhanushali et al, 2011;Maitra et al, 2009), no information is available to date on this variant. The results of our study determine for the first time the frequency of this SNP in the select population from Western India as well as confirm the association with CAD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from South India (AshokKumar et al, 2011), GWAS identified SNPs rs2383207 and rs10757278 at the 9p21 locus and nine additional flanking SNPs were evaluated for increased risk of CAD. In the North Indian population study (Kumar et al, 2010), six SNPs were genotyped in a case-control association study in which three SNPs (rs10116277, rs1333040 and rs2383206) present at the locus 9p21 were significantly associated with CAD.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, independent genome-wide association studies revealed nine highly correlated SNPs (r 2 > 0.8) in a new locus in the region of chromosome 9 (9p21.3), showing the greatest association with heterogeneous CAD of all of the loci analyzed so far (Helgadottir et al, 2007;McPherson et al, 2007;Samani et al, 2007). Since then, numerous studies have confirmed the association of this locus with CAD or myocardial infarction (MI) in populations of European origin (Abdullah et al, 2008;Anderson et al, 2008;Assimes et al, 2008;Lemmens et al, 2009;Koch et al, 2011) as well as Eastern (Shen et al, 2008a;Ding et al, 2009) and Southern Asia origin (AshokKumar et al, 2011). However, genetic heterogeneity was shown in Black subjects (Assimes et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…There are limited studies on the 9p21.3 locus in Asian Indians (7,22,23) where the primary focus has been on genotype/haplotype association of 9p21.3 common variants with CAD. The first ever report published on Asian Indians showed a high frequency of the G allele (0.56) in rs10757278 variant (0.56) and was associated with >2-fold risk for CAD (OR 2.15, 95% confidence interval [CI] 1.02 -4.60) and a high population attributable risk of up to 46% in men (7).…”
Section: Introductionmentioning
confidence: 99%
“…The first ever report published on Asian Indians showed a high frequency of the G allele (0.56) in rs10757278 variant (0.56) and was associated with >2-fold risk for CAD (OR 2.15, 95% confidence interval [CI] 1.02 -4.60) and a high population attributable risk of up to 46% in men (7). The risk attribute of 9p21.3 common allele is said to be modulated by the flanking SNPs in this region (22). In the present study, we have investigated the 9p21.3 locus with respect to the association of five common genetic variants with CAD, compared the relative expression of ANRIL splice variants and other candidate genes in the 9p21.3 locus in a representative case-control cohort of Asian Indians, and finally observing the consequent effect of using short interfering RNA (siRNA) targeted against specific exons in ANRIL, on the neighbouring candidate genes.…”
Section: Introductionmentioning
confidence: 99%